The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1103/physrevlett.118.010402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Direct Path State Characterization by Strongly Measuring Weak Values in a Matter-Wave Interferometer

Abstract: A novel method was recently proposed and experimentally realized for characterizing a quantum state by directly measuring its complex probability amplitudes in a particular basis using so-called weak values. Recently Vallone and Dequal showed theoretically that weak measurements are not a necessary condition to determine the weak value [Phys. Rev. Lett. 116, 040502 (2016)]. Here we report a measurement scheme used in a matter-wave interferometric experiment in which the neutron path system's quantum state was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 51 publications
2
60
0
1
Order By: Relevance
“…When the measured observable corresponds to the projection operator = A 2 or Pauli operator ŝ i (i=x, y, z), the strength of the system-probe interaction can be arbitrarily high [26][27][28][29]. In the former case [26,27,29], the interaction with the optimal coupling strength ξ=π/2, which maximally entangles the total state, can be described as , where P (1) is the probability that the initial state undergoes the transformationT , the system is projected onto y ñ | f , and the probe is projected onto ñ |1 .…”
Section: Other Weak Value Measurement Methods In the Proposed Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…When the measured observable corresponds to the projection operator = A 2 or Pauli operator ŝ i (i=x, y, z), the strength of the system-probe interaction can be arbitrarily high [26][27][28][29]. In the former case [26,27,29], the interaction with the optimal coupling strength ξ=π/2, which maximally entangles the total state, can be described as , where P (1) is the probability that the initial state undergoes the transformationT , the system is projected onto y ñ | f , and the probe is projected onto ñ |1 .…”
Section: Other Weak Value Measurement Methods In the Proposed Frameworkmentioning
confidence: 99%
“…In the former case [26,27,29], the interaction with the optimal coupling strength ξ=π/2, which maximally entangles the total state, can be described as , where P (1) is the probability that the initial state undergoes the transformationT , the system is projected onto y ñ | f , and the probe is projected onto ñ |1 . In the latter case [28], the interaction with the optimal coupling strength ξ=π/ in our framework, and the resulting complex value is y y s á ñ á ñ | | |ˆi f i 2 w , which includes the weak value s á ñ i w . When the measured observable is arbitrary and the strength of the system-probe interaction ξ is arbitrarily high, a modular value is used as the parameter of a pre-and post-selected quantum systems (instead of the weak value) that provides a complete description of its effect on the qubit probe [30].…”
Section: Other Weak Value Measurement Methods In the Proposed Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an analysis performed using the TSVF approach within quantum mechanics suggested that the born/unborn photon has unique physical properties [57,58]. Moreover, recent experiments [59,60] and thought experiments [61][62][63] employ strong rather than weak measurements for analyzing new phenomena. A subsequent work [18], based on Davies et al [57,58], examines through the analysis of weak values the evolution between two strong "no-emission" measure-ments: the wave-function is first weakly radiated and then weakly "drawn back" to its still-excited atom.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither the BKS theorem, nor these experiments, specify which contexts are contradictory. In this article, using recently developed weak measurement techniques in neutron interferometry [14][15][16][17][18][19][20], we experimentally demonstrate which specific measurement context within a BKS-set (Fig. 1a) must contain contradictory value assignments, essentially confining the contextuality [21].…”
Section: Introductionmentioning
confidence: 99%